Internetsicherheit in Europa : Zur Gewährleistung der Netz- und Informationssicherheit durch Informationsverwaltungsrecht - Leisterer, Hannfried (Mohr Siebeck, 2018)
The question of how the law can deal with the problem of internet security is addressed in this volume. Starting with the fact that the internet is structurally insecure, the author finds that the uncertainty this causes must be countered with legal means, particularly when it comes to controlling information about weak spots. Hannfried Leisterer's study examines whether and to what extent information management law can contribute to ensuring internet security.